Fertility preservation in transgender patients. Issue 2 (2nd April 2016) - Jones, C. A.; Reiter, L.; Greenblatt, E.
ABSTRACT: Fertility preservation is an important consideration for transgender people prior to initiating cross-sex hormones or undergoing sex reassignment surgery. We performed a retrospective chart review identifying all transgender patients referred for fertility preservation at one university-affiliated fertility clinic from November 2011 to March 2014. Eleven male-to-female (MtF) transgender patients and 3 female-to-male (FtM) transgender patients were seen for sperm banking or fertility preservation consultation. FtM transgender patients were referred for fertility preservation at a later age and after being on a longer duration of cross-sex hormone therapy than MtF transgender patients. Nine of eleven MtF patients cryopreserved sperm resulting in 1 pregnancy following IVF-ICSI. None of the FtM patients underwent any cryopreservation techniques. This study highlights the need to increase awareness on the effects of age on fertility for FtM patients, and to improve awareness of and access to fertility preservation technologies for all transgender people early on in their transition.